Intraocular lens exchange technique for an opacified bag‐in‐the‐lens. Issue 5 (May 2015) - Dhubhghaill, Sorcha Ní; Van Os, Luc; De Keizer, Rob J.W.; Taal, Michiel; Zakaria, Nadia; Tassignon, Marie‐José
Abstract : N/A: We describe the intraocular lens (IOL) exchange technique that is specific to the bag‐in‐the‐lens IOL. The subsequent IOL analysis displayed a deep granular opacification consisting predominantly of calcium and phosphates that has been described in hydrophilic IOLs. Financial Disclosure : Dr. Tassignon has a proprietary interest in the bag‐in‐the‐lens licensed to Morcher GmbH. No other author has a financial or proprietary interest in any material or method mentioned.